In Silico Study of Active Compounds in Hibiscus Flower Plant (Hibiscus rosa sinensis L.) on Alpha Glucosidase Receptor (3A4A), DPP-4 Receptor (1X70), and PPAR-γ Receptor (5Y2O) as Potential Antidiabetic - Fauziyah, Begum; Dewi, Tanaya Jati Dharma; Rochim, Fatkhur (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 4 (2024): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v4i0.3317, 2025)
The deficiency of insulin hormone or the body's inability to use insulin leads to uncontrolled blood glucose or sugar levels, which is the cause of diabetes mellitus. The ethanol extract of hibiscus flower plant ( Hibiscus rosa sinensis L .) has the ability to reduce blood glucose, suppressing hyperglycemia that causes inflammation. This study aims to evaluate the antidiabetic activity against alpha-glucosidase receptor, DPP-4 (1X70), and PPAR-γ (5Y2O), perform physicochemical predictions, and predict the toxicity of compounds in the Hibiscus rosa sinensis L. flower in silico. Several target proteins in the body related to hyperglycemia diseases are alpha-glucosidase (3A4A), DPP-4 (1X70), and PPAR-γ (5Y2O). The SwissADME software, which uses Lipinski’s Rule of Five parameters, was used for physicochemical predictions. The online software ProTox II and pkCSM were used to predict toxicity. This software refers to LD50 and classifies toxicity classes based on GHS, Ames toxicity, skin sensitivity, and hepatotoxicity. The Molegro Virtual Docker software was used to predict the activity of the compounds. The research results show that two compounds—taraxerol acetate and β-sitosterol xyloside—do not meet Lipinski's Rule of Five parameters. Three compounds are classified in toxicity class 5, three compounds in class 4, and three compounds in class 6. The activity prediction results indicate that β-sitosterol xyloside has the lowest Rerank score compared to the original ligand of alpha-glucosidase, DPP-4, and PPAR-γ receptors, as well as compared to its comparator drug. Therefore, β-sitosterol xyloside can be recommended for further research as an antidiabetic drug candidate.